The Assange agenda : surveillance, democracy and you - Weatherhead, Michael; Rhoades, Lucy Anna; One Planet Pictures; Soundview Media Partners ([Mullumbimby, N.S.W.] : One Planet Films, 2013)
What rights do we have in a world where individuals are under electronic surveillance 24/7? Who really controls the agencies that spy on us? Seeking to explore this unprecedented crisis democracy faces, we hear from key experts including former CIA Officers and whistle blowers, academics and political experts to search for answers to these questions.
Originally released as a documentary in 2013.
Cinematographer, Lynsey Allett ; editors, Brendan Shoebridge, Lynsey Allett ; music, Steve Nossiter.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Assange, Julian; Democracy -- United States; Electronic surveillance -- United States; Documentary films; Nonfiction films; Internet videos; Streaming video